Exploiting crop genotype-specific root-soil interactions to enhance agronomic efficiency - Baggs, Elizabeth M.; Cairns, Jill E.; Mhlanga, Blessing; Petroli, César Daniel; Chamberlin, Jordan; Karwat, Hannes; Kommerell, Victor; Thierfelder, Christian; Paterson, Eric; Gowda, Manje S. (Frontiers in Soil Science, 2023)
Challenges of soil degradation and changing climate pose major threats to food security in many parts of the world, and new approaches are required to close yield and nutrition gaps through enhanced agronomic efficiency. Combined use of mineral fertilizers, organic inputs, improved germplasm and adaptation of these practices to local contexts through improved agronomy can promote efficiency whilst building stocks of soil organic matter (SOM). Within this framework, recent attention has turned to the nature of plant-soil interactions to increase response to mineral fertilizer inputs through utilisation of nutrients from SOM that are replenished through management. This utilisation has been shown in barley and maize to vary with genotype and to be related to root physiological traits associated with rhizodeposition. The identification of candidate genes associated with rhizodeposition takes this a step closer towards the possibility of breeding for sustainability. Here we discuss this potential and feasibility in the context of maize cropping systems, and explore the potential for a combined approach that optimises utilisation of SOM nutrients together with enhanced biological nitrification inhibition to further improve agronomic efficiency.